Supply, installation, fixing of different type of interior finishing items for Brac University new campus building at holding no. Kha 224, Merul Badda, Dhaka-1212. - Brac University (Brac University, 2023)
This agreement made between Brac University and Sthapotto to supply, installation, fixing of different type of interior finishing items for Brac University new campus project.